Methylome and transcriptome analyses reveal HLA-DMB’s contribution to periodontitis development - Bo Zhao; Ronghua Li (PLoS ONE, 2025)
Background Periodontitis is a typical oral disease. Polymorphonuclear neutrophils (PMNs) are crucial immune cells in periodontal tissues, relating to infection, inflammation, and innate immunity. We herein aimed to explore important periodontitis PMN related genes. Methods Periodontitis and control samples were downloaded from Gene Expression Omnibus database, including GSE173082 (methylation data, n=72), GSE10334 (n=127), GSE43525 (n=23), GSE16134 (n=134). Differential expression analysis and differential methylation analysis was employed to find candidate genes. Receiver operating characteristic analysis was performed to evaluate the diagnostic value of the hub gene. The functional pathways were determined by gene set enrichment analysis. Using CIBERSORT software, the immune cell infiltration landscape of periodontitis tissue was explored. The mRNA and protein levels of target gene in clinical tissue samples were determined employing RT-qPCR and western blotting. All statistical analyses were conducted in R software. Results After integrating DNA methylation with transcriptome profiles, GRASP, HLA-DMB, HLA-DMA, CAB39, NCOA2 and TLE4 were identified as candidate genes in periodontitis PMNs. HLA-DMB showed the highest correlation with core DNA methyltransferase DNMT3B (p < 0.05). Between high and low HLA-DMB expression samples, multiple immune related pathways were enriched, and differential immune cell infiltration was observed (p < 0.05). HLA-DMB exhibited significantly higher expressions in both public database and clinical tissue samples (p < 0.05). HLA-DMB was a diagnostic marker for periodontitis (GSE43525 AUC=0.777 and GSE16134 AUC=0.783). Conclusions Significantly higher HLA-DMB expression was noticed in PMNs of periodontitis, which probably contributed to the development of periodontitis. HLA-DMB is a promising diagnostic marker for periodontitis.